Caveolin-1 (P132L), a common breast cancer mutation, confers mammary cell invasiveness and defines a novel stem cell/metastasis-associated gene signature - Bonuccelli, Gloria; Casimiro, Mathew C; Sotgia, Federica; Wang, Chenguang; Liu, Manran; Katiyar, Sanjay; Zhou, Jie; Dew, Elliott; Capozza, Franco; Daumer, Kristin M; Minetti, Carlo; Milliman, Janet N; et al. (The American journal of pathology, 2009)
Here we used the Met-1 cell line in an orthotopic transplantation model in FVB/N mice to dissect the role of the Cav-1(P132L) mutation in human breast cancer. Identical experiments were performed in parallel with wild-type Cav-1. Cav-1(P132L) up-regulated the expression of estrogen receptor-alpha as predicted, because only estrogen receptor-alpha-positive patients have been shown to harbor Cav-1(P132L) mutations. In the context of primary tumor formation, Cav-1(P132L) behaved as a loss-of-function mutation, lacking any tumor suppressor activity. In contrast, Cav-1(P132L) caused significant increases in cell migration, invasion, and experimental metastasis, consistent with a gain-of-function mutation. To identify possible molecular mechanism(s) underlying this invasive gain-of-function activity, we performed unbiased gene expression profiling. From this analysis, we show that the Cav-1(P132L) expression signature contains numerous genes that have been previously associated with cell migration, invasion, and metastasis. These include i) secreted growth factors and extracellular matrix proteins (Cyr61, Plf, Pthlh, Serpinb5, Tnc, and Wnt10a), ii) proteases that generate EGF and HGF (Adamts1 and St14), and iii) tyrosine kinase substrates and integrin signaling/adapter proteins (Akap13, Cdcp1, Ddef1, Eps15, Foxf1a, Gab2, Hs2st1, and Itgb4). Several of the P132L-specific genes are also highly expressed in stem/progenitor cells or are associated with myoepithelial cells, suggestive of an epithelial-mesenchymal transition. These results directly support clinical data showing that patients harboring Cav-1 mutations are more likely to undergo recurrence and metastasis.